2020
DOI: 10.3389/fimmu.2019.03061
|View full text |Cite
|
Sign up to set email alerts
|

Neuraxial Cytokines in Pain States

Abstract: A high-intensity potentially tissue-injuring stimulus generates a homotopic response to escape the stimulus and is associated with an affective phenotype considered to represent pain. In the face of tissue or nerve injury, the afferent encoding systems display robust changes in the input-output function, leading to an ongoing sensation reported as painful and sensitization of the nociceptors such that an enhanced pain state is reported for a given somatic or visceral stimulus. Our understanding of the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 230 publications
(208 reference statements)
3
77
1
4
Order By: Relevance
“…We also observed younger age was associated with MSMP, which could be due to higher physical workload and mental stress before retirement in the MSMP group, 24 , 66 supporting what Neupane et al 44 suggested that MSMP in midlife often persisted to old age in a MSMP trajectory study over 28 years. Cytokines are believed to play a role in pain modulation 19 , 42 , 64 ; however, we did not observe any association between MSMP and plasma levels of MIF, IL-6, IL-1β, or TNF-α. Although further studies are needed to confirm this, our findings were consistent with others.…”
Section: Discussioncontrasting
confidence: 90%
“…We also observed younger age was associated with MSMP, which could be due to higher physical workload and mental stress before retirement in the MSMP group, 24 , 66 supporting what Neupane et al 44 suggested that MSMP in midlife often persisted to old age in a MSMP trajectory study over 28 years. Cytokines are believed to play a role in pain modulation 19 , 42 , 64 ; however, we did not observe any association between MSMP and plasma levels of MIF, IL-6, IL-1β, or TNF-α. Although further studies are needed to confirm this, our findings were consistent with others.…”
Section: Discussioncontrasting
confidence: 90%
“…In the first week after nerve injury, macrophages flow into DRG [34]. Currently, it is known that in addition to resident and recruited immune cells present throughout the neuraxis, cytokines are released from neuronal cells [35]. Thus, cytokines compose a communication network between immune and neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cytokines compose a communication network between immune and neuronal cells. Interleukins (IL-1beta, IL-18 and IL-6) are recognized as the first pronociceptive cytokines in neuropathy [ 35 ] and are known to be strongly activated upon neural damage in the CNS and PNS [ 35 39 ]. In our previous studies, we showed that minocycline administered ip has an analgesic effect in parallel with diminished immunological factors, such as IL-1beta and IL-18 in DRG [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Los mecanismos inmunes cada vez están teniendo más protagonismo en la fisiopatología del dolor neuropático, y diversas citoquinas y quimioquinas parecen jugar un papel importante a nivel del sistema nervioso periférico y central por su efecto pronociceptivo (8). Sabemos que en el ganglio de la raíz dorsal, donde se encuentra en núcleo celular, tiene lugar una gran actividad metabólica que rige la nocicepción.…”
Section: Correspondenciaunclassified